(untitled) (Damascus University Journal of agriculture sciences, 2021)
A field study was carried out at Abi Jarash Farm, Faculty of Agriculture, Damascus, during the growing season 2017-2018, in order to study the effect of four nitrogen fertilizer rates (Urea 46% pure nitrogen N) (0.0, 100, 120, 140, 160 kg N ha-1), which were added during different developmental stages, under irrigated and rainfed conditions, for four locally cultivated varieties, two of which are soft wheat [Doma2 (ACSAD885) and Duma4 (ACSAD 901)], and two durum wheat varieties [Duma1 (ACSAD1105) and Duma3 (ACSAD1229)], on some physical and qualitative characteristics of the grains resulting from the field study. The experiment was laid out according to the Randomized Complete Block Design (RCBD), with the arrangement of split block design, with three replications. The mean ratio of the length of the grain to its width was significantly higher under rainfed conditions for the durum wheat cultivar Douma1 at the nitrogen fertilization rate of 160 kg N ha-1 when the whole amount of nitrogen fertilizers was added at the planting time (2.55), while it was significantly the lowest under irrigated conditions for the bread wheat variety Douma4 at the nitrogen fertilization rate of 140 kg N ha-1 when nitrogenous fertilizer was added at (50% at the time of planting + 50% at the beginning of the tillering; 100% the beginning of tillering) (1.55, 1.57 respectively). The mean seed size was significantly higher under irrigated conditions for the durum wheat cultivar Douma1 at the nitrogen fertilizer rate of 140 kg N ha-1 when nitrogen fertilizer was added at (50% at planting time + 50% at the beginning of flowering) (67.92mm3), while it was significantly the lowest under rainfed conditions for the bread wheat variety Douma2 at the nitrogenous fertilizer rate of 100 kg N ha-1 when the whole amount of nitrogen fertilizer was added at the beginning of flowering (34.71 mm3). The mean grain protein content was significantly higher under rainfed conditions for the durum wheat variety Douma1 at the nitrogen fertilizer rate of 120 and 160 kg N ha-1 when the whole amount of nitrogen fertilizer was added at the beginning of flowering without significant differences between them (18.77, 17.85% respectively), while they were significantly lower under irrigated conditions for the bread wheat cultivar Douma4 in the control treatment (9.10%).The mean specific weight of the grains was significantly higher under irrigated conditions for the bread wheat variety Douma4 at the nitrogen fertilizer rate of 140 kg N ha-1 and when nitrogen fertilizer was added at (50% at the time of planting + 50% at the beginning of the tillering) (89.25 kg Hectoliters-1), whereas it was significantly the lowest under rainfed conditions in the control treatment (without nitrogen fertilization) for the tow durum wheat varieties Douma1 and Douma3 (68.00, 69.36 kg Hectoliter -1 respectively) without significant differences between them.